Advances in neuropsychological assessment of sport-related concussion. Issue 5 (11th March 2013) - Echemendia, Ruben J; Iverson, Grant L; McCrea, Michael; Macciocchi, Stephen N; Gioia, Gerard A; Putukian, Margot; Comper, Paul
Abstract : Objective: To critically review the literature from the past 12 years regarding the following key issues in sports-related neuropsychological assessment: (1) the advantages and disadvantages of different neuropsychological assessment modalities; (2) the evidence for and against the current paradigm of baseline/postinjury testing; (3) the role of psychological factors in the evaluation and management of concussion; (4) advances in the neuropsychological assessment of children; (5) multi-modal assessment paradigms; (6) the role of the neuropsychologist as part of the sports healthcare team and (6) the appropriate administration and interpretation of neuropsychological tests. Design: Targeted computerised literature review (MEDLINE, PubMed, CINAHL and PsychInfo) from 2000 to the present using key words: neuropsychological, neurocognitive, assessment, testing, concussion and sports. Results: More than 2600 articles were identified using key word searches of the databases, including many duplicates. Several books were also reviewed. The articles were pared down for review if they specifically addressed the key areas noted above. Conclusions: Traditional and computerised neuropsychological tests are useful in the evaluation and management of concussion. Brief cognitive evaluation tools are not substitutes for formal neuropsychological assessment. At present, there is insufficient evidence to recommend the widespread routine use of baseline neuropsychological testing. Although scant, research suggests that psychological factors may complicate and prolong recovery from concussion in some athletes. Age-appropriate symptom scales for children have been developed but research into age-appropriate tests of cognitive functions lags behind. Neuropsychologists are uniquely qualified to interpret neuropsychological tests and can play an important role within the context of a multifaceted-multimodal approach to manage sports-related concussions.